AN ANALYSIS OF SABRI ESAT SIYAVUŞGIL’S YOLCULUK POEM IN THE CONTEXT OF GASTON BACHELARD’S POETICS OF SPACE - GÜLTEKİN, Mustafa (Atlas Journal, 2021)
Sabri Esat Siyavuşgil, who was one of the founders of the Yedi Meşaleciler community, portrayed spaces as living things that witness the lives of people in the poems written with syllabic meter in his poetry book titled Odalar ve Sofalar and tried to reflect a subjective and inner reality in these poems. According to this point of view, which reflects the characteristics of expressionism, the poet should reflect the environment in which he lives from a subjective and internal perspective, rather than an objective point of view, since the facts vary from person to person. Because of this subjective nature of reality, analyzing imagination peculiar to poetry from an objective point of view suggested by quantitative analysis is insufficient at the stage of creating a metaphysics of imagination. Therefore, in order to understand the psychological action of a poem, the poetic imagination should be analyzed by using a phenomenological method. In this study, Sabri Esat Siyavuşgil’s Yolculuk poem is analyzed by using the phenomenological analysis method, which is explained in Gaston Bachelard’s The Poetics of Space. As a result of the phenomenological analysis, the phenomena of “being inside the house” and “being outside the house” in Siyavuşgil’s Yolculuk poem are presented with their phenomenological meanings and interpretations.